2004
DOI: 10.1128/jb.186.16.5400-5409.2004
|View full text |Cite
|
Sign up to set email alerts
|

Isoleucine Biosynthesis in Leptospira interrogans Serotype lai Strain 56601 Proceeds via a Threonine-Independent Pathway

Abstract: Three leuA-like protein-coding sequences were identified in Leptospira interrogans. One of these, the cimA gene, was shown to encode citramalate synthase (EC 4.1.3.-). The other two encoded ␣-isopropylmalate synthase (EC 4.1.3.12). Expressed in Escherichia coli, the citramalate synthase was purified and characterized. Although its activity was relatively low, it was strictly specific for pyruvate as the keto acid substrate. Unlike the citramalate synthase of the thermophile Methanococcus jannaschii, the L. int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 40 publications
1
59
2
Order By: Relevance
“…These extracts contained 5.94 Ϯ 0.49 nmol mg Ϫ1 min Ϫ1 of citramalate synthase activity, measured as the pyruvate-dependent release of CoA from acetyl-CoA (47). The citramalate synthase appeared to have a high affinity for pyruvate, with 52.5% Ϯ 4.9% of the activity remaining when the pyruvate concentration was reduced from 1 mM to 0.1 mM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These extracts contained 5.94 Ϯ 0.49 nmol mg Ϫ1 min Ϫ1 of citramalate synthase activity, measured as the pyruvate-dependent release of CoA from acetyl-CoA (47). The citramalate synthase appeared to have a high affinity for pyruvate, with 52.5% Ϯ 4.9% of the activity remaining when the pyruvate concentration was reduced from 1 mM to 0.1 mM.…”
Section: Resultsmentioning
confidence: 99%
“…In the spirochete Leptospira interrogans and in methanogenic Archaea, the key isoleucine precursor, 2-oxobutanoate, is synthesized from acetyl-CoA and pyruvate via the citramalate pathway (17,34,47) (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, DET0825 is in a gene cluster with other key genes associated with leucine/ isoleucine synthesis, including DET0826 (LeuB), DET0827 (LeuD), DET0828 (LeuC), and DET0830 (LeuA). Previous studies on a similar alternative isoleucine biosynthesis pathway in Leptospira interrogans showed that ␣-isopropylmalate isomerase (EC 4.2.1.33) (LeuC/D) and ␤-isopropylmalate dehydrogenase (EC 1.1.1.85) (LeuB) are functional in the biosynthesis of both leucine and isoleucine (42). That DET0825 to DET0828 are present in the same operon (www .microbesonline.org/operon) suggests that they may have coordinated regulation involved in isoleucine and leucine synthesis, since genes in a single pathway frequently reside in the same operon, exhibit similar expression patterns, and share transcriptional regulators (27).…”
Section: Discussionmentioning
confidence: 99%
“…Citramalate may also have a function in Ile biosynthesis by serving as a precursor of 2-oxobutyrate, a substrate for AHAS. This metabolic route has been demonstrated for a mutant of the microorganism Serratia marcescens (Kisumi et al, 1977), the halophilic archeon Haloarcula hispanica (Hochuli et al, 1999), and in Leptospira interrogans (Xu et al, 2004).…”
Section: Ipmss Produce Other Products In Vitro and In Vivomentioning
confidence: 99%